Effect of formicid granulated baits on non-target ants biodiversity in eucalyptus plantations litter - Corassa, Janaína De Nadai; Magistrali, Iris Cristiane; Moreno, Jorge Candido; Cantarelli, Edison Bisognin; Corassa, Anderson (Comunicata Scientiae, 2013)
The effect of systematic use of granulated bait for leaf-cutting ants control was assessed on a community of non-target ants in eucalyptus in the municipality of Vera, Mato Grosso State, Brazil. The ants were collected using the Winkler extractors, in 50 samples of 1 m2 of litter in each stage: eight days before the distribution of baits, eight days after the distribution of baits and subsequently each month, totaling 13 collections. Each sample were taken at distances of 50 meters from each other. Copies of ants were assembled via dry, labeled and identified in genus and species level. The analysis of the residual effect was conducted by comparing the number of individuals and species over the months. A total of 273 ants were distributed into nine genera, four subfamilies  and 13 species. It was found that diversity index at the end of the study period did not return to initial levels observed before treatment with the ant, suggesting that the active ingredient in bait alters the patterns of diversity pre-existing, causing adverse impact on non-target myrmecofauna. This is the first work in this region and serves as support for future studies on ant diversity in leaf litter of Eucalyptus.